2022
DOI: 10.22226/2410-3535-2022-1-71-75
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal effect of strain rate on dynamic recrystallization of austenite in medium carbon steel alloyed by boron

Abstract: According to literature data confirmed by our experiments on various steels, the strain degree that triggers the dynamic recrystallization of austenite in high-temperature deformation increases with the strain rate. However, as shown in the present work, micro-alloying of medium carbon steel by boron results in the opposite dependence in the strain rate range of 1 to 100 s −1 . The corresponding features of stress-strain diagrams comply with the former austenite structures revealed by chemical etching. A speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The strongest effect of boron is seen when its concentration is over 0.0005-0.0008% but does not exceed 0.003-0.005% [22]. Recent studies are also devoted to the effect of boron on hardenability [23][24][25]. For example, Gent et al [23] established a novel datadriven machine learning model and demonstrated that machine learning can predict accurately and efficiently the hardenability curve of boron steel and guide the material design and heat treatment process of advanced boron steel.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest effect of boron is seen when its concentration is over 0.0005-0.0008% but does not exceed 0.003-0.005% [22]. Recent studies are also devoted to the effect of boron on hardenability [23][24][25]. For example, Gent et al [23] established a novel datadriven machine learning model and demonstrated that machine learning can predict accurately and efficiently the hardenability curve of boron steel and guide the material design and heat treatment process of advanced boron steel.…”
Section: Introductionmentioning
confidence: 99%